2014
DOI: 10.1038/jp.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of GutCheckNEC: a clinical risk index for necrotizing enterocolitis

Abstract: Background Better measures are needed to identify infants at risk for developing necrotizing enterocolitis (NEC) and facilitate communication about risk across transitions. Although NEC is multi-factorial, quantification of composite risk for NEC in an individual infant is not clearly defined. Objective This study’s objective was to describe the derivation, validation and calibration testing of a novel clinical NEC risk index, GutCheckNEC. Individual risk factors were weighted to assess composite odds of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 53 publications
0
72
0
4
Order By: Relevance
“…Our study demonstrated an association between PRBC transfusion and onset of NEC in about a quarter of our [16]. A more recent meta-analysis has been more cautious in reaching the same conclusion [17].…”
Section: Discussionmentioning
confidence: 58%
“…Our study demonstrated an association between PRBC transfusion and onset of NEC in about a quarter of our [16]. A more recent meta-analysis has been more cautious in reaching the same conclusion [17].…”
Section: Discussionmentioning
confidence: 58%
“…Two risk reducers, exclusive human milk feeding and probiotic administration, were also factored into the score. The score was derived from data from about 35,000 infants, calibrated in 23,000 infants, and validated in 120 NEC cases compared to 240 matched controls and shown to discriminate infants that developed severe NEC (receiver operating characteristics area under the curve: 0.83) [13].…”
Section: Risk Assessment For Sepsis and Necmentioning
confidence: 99%
“…The diagnostic parameters used for creating the predictive scoring tool to define NEC severity were chosen from common clinical symptoms and signs associated with suspicion of NEC [12][13][14][15][20][21][22][23][24][25] and are summarized in Table 1. The scoring tool consisted of clinical presentation, radiological and laboratory findings, feeding characteristics and gastric residuals.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] Gephart et al developed GutCheck, a tool used to predict the occurrence of NEC based on evaluating several known risk factors, including gestational age (GA), history of blood transfusions, sepsis, metabolic acidosis and human milk feeding. [12] Similarly, McKeown et al identified clinical parameters such as respiratory changes immediately preceding a diagnosis of NEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation